Novel antibiotics for the treatment of Staphylococcus aureus. Issue 6 (November 2009) - Ohlsen, Knut
Staphylococcus aureus is a leading cause of nosocomial and community-acquired infection associated with significant morbidity and mortality. Antibiotic treatment of infections owing to S. aureus have become increasingly challenging as the pathogen has acquired a broad spectrum of antibiotic resistance mechanisms. In particular, emergence and spread of methicillin-resistant S. aureus (MRSA) progressed to a global health threat. The glycopeptides antibiotics vancomycin and teicoplanin have remained as the drugs of last resort for more than 20 years. Fortunately, in addition to the glycopeptides, several novel antibiotics including linezolid, daptomycin, tigecycline, quinupristin/dalfopristin and ceftobiprole acting against MRSA have been recently introduced into clinical practice broadening therapeutic options. Although the arsenal of antistaphylococcal drugs has filled up in recent years, the rate of MRSA infection continues to be high in most countries. This demands an ongoing search for new antibacterials and lead compounds as well as development of alternative therapies and faster diagnostics to ensure effective anti-staphylococcal therapy in the future.